A Multidisciplinary Approach in Prenatal Diagnosis of TSC With Cardiac Rhabdomyoma as the Initial Symptom - Qi, Yiming; Ding, Hongke; Huang, Yanlin; Zeng, Yukun; Yu, Lihua; Liu, Ling; Zhang, Yan; Yin, Aihua (Frontiers in Pediatrics, 2021)
The long-term prognosis of fetus with cardiac rhabdomyoma (CR) depends on the correlation with tuberous sclerosis complex(TSC). Recent years, numerous variations of uncertain significance (VUS) of TSC genes produced by high-throughput sequencing makes counseling challenging, studies until now tend to sidestep the tricky topics. Here, we integrated detailed parental phenotype, echocardiography, neuro MRI and genetic information to conduct a comprehensive evaluation for 61 CR fetuses. As a result, multiple CRs and cerebral lesions appeared in 90% and 80% respectively in fetuses with pathogenic(P)/likely pathogenic(LP) TSC1/TSC2 variation. 85.7% of the live-born with P/LP presented TSC-associated signs. 85.7% VUS without nervous findings had good prognosis. Genetic evidence and cerebral MRI findings are the most sensitive index to assess long-term prognosis, which complement and confirm each other for a TSC diagnosis. 68.9% fetuses with CR could benefit from this multidisciplinary approach, which turned to be potentially clinically actionable with precise clinical/genetic diagnosis or had a foreseeable outcome. Our practice provides a practical and feasible solution for perinatal management and prognostic guidance for fetuses with CR.